Case report: Electrocardiographic (ECG) recording during the hanging process - Ungermann, Emily Marie; Balikowski, Marek; Hemker, Jan; Feld, Kristina (Forensic science, medicine, and pathology, 2024)
A 48-year-old woman was found hanged in the bathroom. She was wearing a Holter monitor, which was later analysed by a cardiologist. During autopsy, findings congruent with atypical hanging were collected. The ECG showed a 20 s asystole and four minutes later bradycardia, which progressed to a second-degree AV-block Mobitz I, then Mobitz II, then to a third-degree AV-block. Finally, only P waves could be observed, before heart action ceased. This is one of few cases reporting ECG-changes during hanging and might give further insight into the complex pathophysiology of this type of death.